A Heat-Map-Based Algorithm for Recognizing Group Activities in Videos - Lin, Weiyao; Chu, Hang; Wu, Jianxin; Sheng, Bin; Chen, Zhenzhong (IEEE transactions on circuits and systems for video technology, 2013)
In this paper, a new heat-map-based algorithm is proposed for group activity recognition. The proposed algorithm first models human trajectories as series of heat sources and then applies a thermal diffusion process to create a heat map (HM) for representing the group activities. Based on this HM, a new key-point-based (KPB) method is used for handling the alignments among HMs with different scales and rotations. A surface-fitting (SF) method is also proposed for recognizing group activities. Our proposed HM feature can efficiently embed the temporal motion information of the group activities while the proposed KPB and SF methods can effectively utilize the characteristics of the HM for activity recognition. Section IV demonstrates the effectiveness of our proposed algorithms.